DPP-4 inhibitors for treating T2DM - hype or hope? an analysis based on the current literature - Saini, Kunika; Sharma, Smriti; Khan, Yousuf (Frontiers in Molecular Biosciences, 2023)
DPP-4 inhibition is an interesting line of therapy for treating Type 2 Diabetes Mellitus (T2DM) and is based on promoting the incretin effect. Here, the authors have presented a brief appraisal of DPP-4 inhibitors, their modes of action, and the clinical efficiency of currently available drugs based on DPP-4 inhibitors. The safety profiles as well as future directions including their potential application in improving COVID-19 patient outcomes have also been discussed in detail. This review also highlights the existing queries and evidence gaps in DPP-4 inhibitor research. Authors have concluded that the excitement surrounding DPP-4 inhibitors is justified because in addition to controlling blood glucose level, they are good at managing risk factors associated with diabetes.